1991
DOI: 10.1007/bf00016076
|View full text |Cite
|
Sign up to set email alerts
|

Environmental conditions differentially affect vir gene induction in different Agrobacterium strains. Role of the VirA sensor protein

Abstract: The induction of vir gene expression in different types of Agrobacterium strains shows different pH sensitivity profiles. The pH sensitivity pattern demonstrated by octopine Ti strains was similar to that of a supervirulent leucinopine Ti strain, whereas this was different from that shown by nopaline Ti strains and agropine Ri strains. Data are given which indicate that these differences are due to different properties of the virA genes of these wild types. An exceptional case was formed by strains with the li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
2

Year Published

1992
1992
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(32 citation statements)
references
References 35 publications
1
29
2
Order By: Relevance
“…the two distinct pH values which had been characterized as optimal for induction of nopaline-type or octopine-type vir genes. Indeed, previous investigators (39) had shown that the optimal pH for induction by acetosyringone of the vir genes of pTiC58 and pTiB6 was 5.8 and 5.3, respectively. No induction was noted at pH 6.8 (39).…”
Section: Resultsmentioning
confidence: 96%
“…the two distinct pH values which had been characterized as optimal for induction of nopaline-type or octopine-type vir genes. Indeed, previous investigators (39) had shown that the optimal pH for induction by acetosyringone of the vir genes of pTiC58 and pTiB6 was 5.8 and 5.3, respectively. No induction was noted at pH 6.8 (39).…”
Section: Resultsmentioning
confidence: 96%
“…One aspect of pilus biology that may be important for transformation is its temperature lability. Although vir gene induction is maximal at approximately 25 to 27°C (8,162,323), the pilus of some, but not all, Agrobacterium strains is most stable at lower temperatures (approximately 18 to 20°C) (18,105,188). Early experiments by Riker indicated a temperature effect on transformation (268).…”
Section: How Is T-dna Transferred From Agrobacteriummentioning
confidence: 99%
“…However, those studies were done in vitro after pH adjustment of the extracts and so may not reflect the situation in planta. This is especially relevant since Turk et al (41) have shown that octopine-and nopaline-type VirA proteins differ in their pH requirements for optimal vir induction. Thus, it may be that cereal sap is more compatible with the functioning of nopaline-type VirA than octopine-type VirA.…”
Section: Discussionmentioning
confidence: 99%